2014
DOI: 10.5717/jenb.2014.18.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aquatic exercise and CES treatment on the changes of cognitive function, BDNF, IGF-1, and VEGF of persons with intellectual disabilities

Abstract: [Purpose]The purpose of this study was to investigate the effects of aquatic exercise and CES treatment on the cognitive function by using K-WAB and BDNF, IGF-1, and VEGF of persons with intellectual disabilities.[Methods]All subjects were 15 male with intellectual disabilities who were participating in the aquatic training program and CES treatment during 12 weeks at rehabilitation center. The subjects were divided into control group, exercise group, and exercise+CES group. Blood samples for BDNF, IGF-1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As generally the less initial level, the greater evolutionary mage (Sibley and Beilock 2007), the greater cognitive functions improvement in individuals with ID compared with controls could be explained by their lower BDNF level resulting in decreased complex cognitive functions (Han et al 2013). More importantly, Lee et al (2014b) showed that physical exercise increases the blood BDNF in individuals with ID and this increase was associated with the rise of WM after exercise (Lee et al 2014b). In addition, BDNF concentration acted on hippocampal function (Liu and Nusslock 2018) that had a crucial role in visual-spatial memory especially in Corsi test (Toepper et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As generally the less initial level, the greater evolutionary mage (Sibley and Beilock 2007), the greater cognitive functions improvement in individuals with ID compared with controls could be explained by their lower BDNF level resulting in decreased complex cognitive functions (Han et al 2013). More importantly, Lee et al (2014b) showed that physical exercise increases the blood BDNF in individuals with ID and this increase was associated with the rise of WM after exercise (Lee et al 2014b). In addition, BDNF concentration acted on hippocampal function (Liu and Nusslock 2018) that had a crucial role in visual-spatial memory especially in Corsi test (Toepper et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, Lee et al . (2014b) showed that physical exercise increases the blood BDNF in individuals with ID and this increase was associated with the rise of WM after exercise (Lee et al . 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Of all the neurotrophins, BDNF is considered most susceptible to regulation by exercise and physical activity, and it acts at the interface of metabolism and brain plasticity [1,132]. Consequently, exercise and BDNF have been associated with reduced symptoms of depression and the promotion of cognitive enhancement [141]. Therefore, exercise can influence the epigenome to reduce depression and enhance cognitive abilities [1,7,142].…”
Section: Effects Of Dehydrationmentioning
confidence: 98%
“…The chronic aquatic exercise programs ranged from 7 days to 6 months, whereas several studies employed a single bout of aquatic exercise [9,14]. Most of the aquatic exercise programs focused on aquatic exercise alone, whereas some evaluated it in combination with cranial electrotherapy stimulation [8], cognitive training [15][16], and land-based exercise training [17]. The cognitive outcomes varied, including global measures of cognition (e.g., MMSE; Mini-Mental State Exam), executive function, attention, learning and memory, language fluency, cognitive communication, cerebral oxygenation, and biomarkers (e.g., BDNF (brain-derived neurotrophic factor), VEGF (vascular endothelial growth factor), IGF-1 (insulin-like growth factor-1)) of cognitive function.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 13 studies, 12 were experimental studies, whereas one was a case study [12]. Among the 12 experimental studies, 9 were conducted among middle-age to older adults, with 2 occurring among children/adolescents [7][8] and 1 among young adults [9]. Samples included healthy individuals, as well as those with intellectual disabilities [8], ADHD (attention deficit hyperactive disorder) [7], fibromyalgia [10][11], mild cognitive impairment [9], Alzheimer's disease [12], and multiple sclerosis [13].…”
Section: Methodsmentioning
confidence: 99%